Panic scrip of 1893, 1907 and 1914 : an illustrated catalog of emergency monetary issues - Shafer, Neil.; Sheehan, Tom.; Reed, Fred. (Jefferson, North Carolina : McFarland & Company, Inc., 2013)
"This extensively illustrated work catalogs all known U.S. emergency currency issues of the panics of 1893, 1907 and 1914. Nearly 900 photographs show most types of these privately produced substitutes for money. The book includes contextual historical information and authoritative appendices by Steve Whitfield on labor scrip and Loren Gatch on the background leading to these currency issues"--
pt. 1. Scrip from the panic of 1893 -- pt. 2. Scrip from the panic of 1907 -- pt. 3. Scrip from the financial crisis of 1914.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Emergency currency -- United States -- Catalogs; Money -- United States -- History; Currency crises -- United States -- History; Electronic books